CONSUMER PREFERENCES OF ORGANIC RICE AT THE TOKOPEDIA MARKETPLACE (Agridevina : Berkala Ilmiah Agribisnis, 2022)
Preference is subjective taste for various choices of existing product attributes. Consumer preferences need to be known so that producers can target their consumers in a more focused manner. Therefore, this study aims to analyze consumer preferences for the attributes of organic rice. This study was conducted at Tokopedia marketplace. The sampling method in this study used a non-probability sampling method, namely purposive sampling and obtained 65 respondents. The analysis used in this study is Importance and Performance Analysis (IPA). The results showed that the attributes of organic rice that had the highest importance were the cleanliness of organic rice from objects other than rice, the color of organic rice that was not too white, and the integrity of the grains of organic rice. This means that consumers preferences for organic rice in the Tokopedia marketplace are clean organic rice, organic rice colors that are not too white, and whole grains of organic rice. DOI : https://doi.org/10.33005/agridevina.v11i2.3474